The phenomenology of pain - Geniusas, Saulius (Series in Continental thought ;, 2020)
"The Phenomenology of Pain is the first book-length investigation of its topic to appear in English. Groundbreaking, systematic, and illuminating, it opens a dialogue between phenomenology and such disciplines as cognitive science and cultural anthropology to argue that science alone cannot clarify the nature of pain experience without incorporating a phenomenological approach. Building on this premise, Saulius Geniusas develops a novel conception of pain grounded in phenomenological principles: pain is an aversive bodily feeling with a distinct experiential quality, which can only be given in original first-hand experience, either as a feeling-sensation or as an emotion. Geniusas crystallizes the fundamental methodological principles that underlie phenomenological research. On the basis of those principles, he offers a phenomenological clarification of the fundamental structures of pain experience and contests the common conflation of phenomenology with introspectionism. Geniusas analyzes numerous pain dissociation syndromes, brings into focus the de-personalizing and re-personalizing nature of chronic pain experience, and demonstrates what role somatization and psychologization play in pain experience. In the process, he advances Husserlian phenomenology in a direction that is not explicitly worked out in Husserl's own writings"--